#Bodypositive : performances of body positivity by influencers on Instagram : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology (Health Endorsement) at Massey University, Albany Campus, Aotearoa/New Zealand - Jones, Aroha Moana (Massey University, 2019)
Women around the world are increasingly using the social media platform Instagram, a popular photo-sharing application, to promote body acceptance and address unrealistic appearance-related ideals. Drawing on ideas of performance and performativity (Butler, 1988, 1990; Goffman, 1959, 1976) this research examines the performative practices and performances of body positive influencers on Instagram and considers how influencers are self-presenting, both visually and textually, to discursively construct and produce body positive identities. I interpreted the performances of body positive influencers as meaningful practices of resistance that offer promising moments of instability and threaten to destabilise narrow, predominantly white, Western, hetero-normative beauty standards, including the thin-ideal. Instagram appears to offer body positive influencers a productive space for reimagining and re-imaging the ways that bodies are enacted and performed. However, despite this, influencers occasionally slip from body positive discourses to pre-existing discourses of idealised female beauty and conventional feminine rhetoric, thus, at times repeating and (re)producing the very ideologies they purport to reject. An unexpected finding of this research was that many of the influencers discussed body positivism alongside deeply personal accounts of recovery from eating disorders and disordered eating. This thesis is unique and distinguished from previous research, in that it explores body positivity in the context of eating disorder recovery. Key findings are that the current iteration of body positivity on Instagram can be read as an undertaking that troubles hegemonic norms of female beauty, facilitates corporeal performances of resistance, and opens a new space for the performance, documentation, and discussion of recovery.
Keywords: Instagram (Firm); Body image in women; Influence (Psychology); Feminine beauty (Aesthetics); Eating disorders in women